Imaging Features with Histopathologic Correlation of CNS High-Grade Neuroepithelial Tumors with a BCOR Internal Tandem Duplication - Cardoen, L.; Tauziède-Espariat, A.; Dangouloff-Ros, V.; Moalla, S.; Nicolas, N.; Roux, C.-J.; Bouchoucha, Y.; Bourdeaut, F.; Beccaria, K.; Bolle, S.; Pierron, G.; Dufour, C.; et al. (American Journal of Neuroradiology, 2022)
BACKGROUND AND PURPOSE: A new brain tumor entity occurring in early childhood characterized by a somatic BCL6 corepressor gene internal tandem duplication was recently described. The aim of this study was to describe the radiologic pattern of these tumors and correlate this pattern with histopathologic findings.MATERIALS AND METHODS: This retrospective, noninterventional study included 10 children diagnosed with a CNS tumor, either by ribonucleic acid–sequencing analysis or deoxyribonucleic acid methylation analysis. Clinical, radiologic, and histopathologic data were collected. A neuropathologist reviewed 9 tumor samples. Preoperative images were analyzed in consensus by 7 pediatric radiologists.RESULTS: All tumors were relatively large (range, 4.7–9.2 cm) intra-axial peripheral masses with well-defined borders and no peritumoral edema. All tumors showed mild and heterogeneous enhancement and marked restriction on DWI of the solid portions. Perfusion imaging showed a relatively lower CBF in the tumor than in the adjacent normal parenchyma. Nine of 10 tumors showed areas of necrosis, with the presence of hemorrhage in 8/10 and calcifications in 4/7. Large intratumoral macroscopic veins were observed in 9/10 patients. No intracranial or spinal leptomeningeal dissemination was noted at diagnosis.CONCLUSIONS: CNS tumors with a BCL6 corepressor gene internal tandem duplication present as large intra-axial peripheral masses with well-defined borders, no edema, restricted diffusion, weak contrast enhancement, frequent central necrosis, hemorrhage and calcifications, intratumoral veins, and no leptomeningeal dissemination at the time of diagnosis. Knowledge of these imaging characteristics may aid in histologic, genomic, and molecular profiling of brain tumors in young children.ITDinternal tandem duplication